2014
DOI: 10.1161/atvbaha.113.302573
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Protein L13a Deficiency in Macrophages Promotes Atherosclerosis by Limiting Translation Control-Dependent Retardation of Inflammation

Abstract: Objective Unresolved inflammatory response of macrophages plays a pivotal role in the pathogenesis of atherosclerosis. Previously we showed that ribosomal protein L13a-dependent translational silencing suppresses the synthesis of a cohort of inflammatory proteins in monocytes and macrophages. We also found that genetic abrogation of L13a expression in macrophages significantly compromised the resolution of inflammation in a mouse model of LPS-induced endotoxemia. However, its function in the pathogenesis of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 45 publications
(65 reference statements)
1
46
4
Order By: Relevance
“…We previously used a cellular model of human monocytes 13 and an animal model of myeloid-specific L13a KO mice 15 to show the ability of L13a-dependent translational silencing to block the translation of different chemokine and chemokine receptors harboring GAIT elements in the 3'UTRs of the mRNA. Using animal models of LPS-induced endotoxemia 15 and high-fat diet-induced atherosclerosis, 16 we also showed the potential of this mechanism to resolve physiological inflammation. These studies are consistent with emerging evidence from other groups regarding the importance of translational control in innate immunity and inflammation.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…We previously used a cellular model of human monocytes 13 and an animal model of myeloid-specific L13a KO mice 15 to show the ability of L13a-dependent translational silencing to block the translation of different chemokine and chemokine receptors harboring GAIT elements in the 3'UTRs of the mRNA. Using animal models of LPS-induced endotoxemia 15 and high-fat diet-induced atherosclerosis, 16 we also showed the potential of this mechanism to resolve physiological inflammation. These studies are consistent with emerging evidence from other groups regarding the importance of translational control in innate immunity and inflammation.…”
Section: Discussionmentioning
confidence: 90%
“…The polysomes were resolved, and the chemokine mRNAs were identified in the fractions using previously established methods. 15,16 GAIT element-mediated translational silencing was determined using a previously reported protocol. 15 Identification of live bacteria in the circulation of the DSStreated mice Blood was isolated from mice fed 3% DSS (w/v) in the drinking water through cardiac puncture into tubes containing 0.1 M EDTA.…”
Section: Identification Of Macrophages From Isolated Intestinal Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…68 Using this approach with mice expressing LysM Cre recombinase, Basu et al 69 found that genetic depletion of ribosomal protein L13a in macrophages augmented atherosclerosis in mice.…”
Section: Inflammation In Atherosclerosismentioning
confidence: 99%